Motorcycle-Security using Position Searching Algorithm Based on Hybrid Fuzzy-Dijkstra - Rofiq Mubarok; Dwi Verdy Firmansyah; Dheny Haryanto; Noor Pratama Apriyanto; Umniyatul Mahmudah; Iswanto Iswanto (Institute of Advanced Engineering and Science, 2016)
Motorcycle safety system has been provided by the manufacturer in the form of a handlebar lock and electrical key equipped with alarms. Keys provided by the manufacturers sometimes fail in securing a motorcycle. In addition the safety system does not provide position information of the stolen motorcycle to the owner. With these problems, the paper presents safety locked motorcycle equipped with artificial intelligence algorithms. Artificial intelligence algorithm is used to find and detect the location of the motorcycle using the shortest path algorithm. This paper applies search algorithm using Dijkstra algorithm where the algorithm is used to make the decision to get the location of the motorcycle. By using the algorithm, the location of the motorcycle can be detected but it is not able to find the shortest path needed. Therefore, this paper describes the modification of Dijkstra algorithm by adding a Fuzzy algorithm that is used for the weight values in decision making, so that it can pursue to find the shortest path.